Benessere e malattia in medicina estetica. Il superamento di una dicotomia ed il ruolo del medico (TEST BioLaw Journal - Rivista di BioDiritto, 2014)
The market for aesthetic medicine is constantly growing and, except “reconstructive” surgery that responds exclusively to the need to improve the appearance, it presents a number of legal, but also strictly ethical and professional questions. The aim of the authors is, through a literature review, to discuss whether it can still be possible to deal with an idea of aesthetic medicine extraneous to the concept of disease and, therefore, to re-evaluate the position of the aesthetic surgeon with its authoritative professional dignity.
Keywords: Aesthetic medicine; ethics; definition of disease; duty of care; doctor-patient relationship